2014
DOI: 10.1055/s-0034-1385024
|View full text |Cite
|
Sign up to set email alerts
|

Optische Kohärenztomografie (OCT) – ein neues diagnostisches Instrument in der Psychiatrie?

Abstract: Optical coherence tomography (OCT) is a non-invasive, contact-less imaging method which provides an "in vivo" representation of the retina. It allows the quantitative measurement of retinal nerve fibre layer thickness (RNFLT) and macula thickness (MT) and, in addition, is suitable to measure volumes (e.g., macula volume/MV). In the research of neurodegenerative diseases, OCT has been increasingly used and has shown its potential as a possible diagnostic tool over the course of the last few years. In recent yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…After duplicates were manually removed, the search retrieved 591 references, of which 32 systematic reviews were obtained in full text. Eighteen of these were excluded for 1 or more of the following reasons: published before 2016 (7 reviews); used surrogates of dementia as a target condition (1 review); used ocular conditions as biomarker, rather than test technique results (2 reviews); and absence of meta-analyses (10 reviews). Five reviews published before 2016 reported on OCT and 2 on retinal microvascular changes .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After duplicates were manually removed, the search retrieved 591 references, of which 32 systematic reviews were obtained in full text. Eighteen of these were excluded for 1 or more of the following reasons: published before 2016 (7 reviews); used surrogates of dementia as a target condition (1 review); used ocular conditions as biomarker, rather than test technique results (2 reviews); and absence of meta-analyses (10 reviews). Five reviews published before 2016 reported on OCT and 2 on retinal microvascular changes .…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen of these were excluded for 1 or more of the following reasons: published before 2016 (7 reviews); used surrogates of dementia as a target condition (1 review); used ocular conditions as biomarker, rather than test technique results (2 reviews); and absence of meta-analyses (10 reviews). Five reviews published before 2016 reported on OCT and 2 on retinal microvascular changes . Consistent with our expectations, the number of included studies in these reviews was much lower than that in the most recent systematic reviews on the same techniques.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14] OCT has also shown efficacy as a diagnostic tool in psychiatric disorders, such as schizophrenia and MDD. [15][16][17][18] However, the relationship between retinal changes measured by OCT and depression remains unknown. The present study aims to conduct a systematic review and meta-analysis to investigate this association and also identify potential diagnostic biomarkers of depression through OCT.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Several studies have also employed OCT to reveal that retinal layer thickness is reduced in patients with depression 12–14. OCT has also shown efficacy as a diagnostic tool in psychiatric disorders, such as schizophrenia and MDD 15–18…”
Section: Introductionmentioning
confidence: 99%